Penyuluhan Peran Pemerintah Desa dalam Mendorong Kompetensi Kewirausahaan Pelaku Usaha Penjual Jagung Rebus di Desa Amesiu - Anto, Rola Pola; Rahmatyah, Sitti; Amir, Muhammad; Gunawan, Gunawan; Sahili, La Ode; Habiba, Nurul; Saputri, Atisah (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
The role of the Amesiu Village government is urgently needed in encouraging the entrepreneurial competency of Boiled Corn Seller (BCS) business actors. The purpose of counseling on the role of the village government in encouraging entrepreneurial competence for BCS in Amesiu Village is to provide information and understanding to BCS business actors so that the business they develop can increase with the role of the Amesiu Village government. Counseling was carried out in Amesiu Village. The method used in the implementation of counseling is the lecture and question and answer method. The target in the counseling activity was the BCS in Amesiu Village as many as 25 people. The results of the counseling show that the responses of the participants after attending the counseling materials from the informants were very useful in supporting technical, marketing, financial, and human relations competencies. Basically counseling on the role of the village government in encouraging entrepreneurial competency at BCS in Amesiu Village specifically has a positive impact on business actors in Amesiu Village. Suggestions for further community service activities can be carried out through training so that participants are actively involved in solving the problems of the business being developed.